Efecto del pre-secado sobre el porcentaje de fermentación y calidad sensorial del licor de cacao theobroma cacao l - Jimenez Collaguazo, Juan Carlos (2017)
Cacao (Theobroma cacao L.) in Ecuador represents 5% of production worldwide, creating income and employment for many people from different provinces. Cocoa because of its climatic and geographical conditions, Ecuador is characterized by being a good producer of cocoa because of its excellent unique organoleptic characteristics fine aroma, our country has a wide range of genetic material whose taste has been recognized at world market level. Our cocoa because of its mismanagement in the post-harvest period we have lost the quality and priority in the international market. The present work was carried out in the clonal cacao bank of the Granja Santa Inés, using the same range of genetic material that is established in the same research area. Taking as an emphasis that all samples of cocoa have the same soil and climatic conditions, there is the same area of research. The main objective was to evaluate the effect of elimination of excess mucilage by pre-drying on the quality of the almonds. 100 healthy and ripe cobs were harvested and harvested, the same day the corn husks were cracked and then placed in a plastic marquee during a rest for 18 hours, after 18 hours Placed in the jute sacks for the fermentation process for a period of 3 days, making the removal every 24 hours. The temperature of the beginning and end of the almonds was also taken into account. As also Ph of the testa and cotyledon of the beginning and end of the fermentation of the almonds. On the other hand, the respective drying of the almonds that were placed for 7 days in marquesinas of plastic meshes, under plastic coating and exposed to the natural air, until reaching between 7 and 8% of humidity. Seven treatments were evaluated in seven jute sacks introduced in pre- dried SCYICM wood box and two non-pre-dried RM wood rotors: (T1) ICS-95 SCYICM, (T2) ETT-103 SCYICM, (T3) CCN-51 SCYICM , (T4) NATIONAL SCYICM, (T5) MIXED SCYICM, and as controls (T6) ICS-95 RM and (T7) CCN-51 RM. It was designed totally randomly with three types of repetitions. To compare the data and to take the average we use the program SPSS, allows us to compare the results obtained with the witness. After the cocoa was fermented, the physical tests were carried out: the percentage of grain, percentage of grains, test and fermentation, in the Laboratory of Plant Health of the Academic Unit of Agricultural Sciences. Regarding the analysis of cocoa liquor, they were sent to the laboratory of the INIAP Pichelingue. After obtaining the data of sensorial analysis of the laboratory, placing the CCN-51 (T3) with 97.67% of good fermentation. Comparing a large difference of 31% to (T6) that obtained a lower percentage of fermentation. For which pre-drying was not performed allowing a low percentage of fermentation. The (T6) with its value 66.67%, so no pre-drying was performed. The best sensory profile was presented (T3), with good and acceptable ratings with respect to the sensory analyzes, the T1 and T5 scores high on bitter taste, acidity and astringent. It is recommended to implement the method that helps to lower the percentage of bitterness and astringency to obtain good results in terms of sensory quality of cocoa.